Interest and need for continuing medical education in pediatric complementary and integrative medicine: a cross-sectional survey from Switzerland - Benedikt M. Huber; Pierre-Yves Rodondi (BMC, 2022)
Abstract Background Pediatric integrative medicine, combining conventional and complementary medical approaches for children and adolescents, is an integral part of the health care system in Switzerland. However, there is still a lack of complementary and integrative medicine topics in training and continuing educational programs. For the first time on a national level, the 2021 annual conference of the Swiss Society of Pediatrics was entirely dedicated to the topic of integrative medicine. Methods Using a cross-sectional online survey, this study investigated congress participants' evaluation and feedback with the aim to assess whether the program had met their objectives and to get empirical data on their attitude, expectations and needs regarding pediatric complementary and integrative medicine. Descriptive methods were used to present the results. Results Among 632 participants of the conference, 228 completed the evaluation form (response rate 36%). The overall feedback about the congress and the main theme of pediatric integrative medicine was clearly positive. The majority of respondents had achieved their educational objectives including complementary and integrative medicine issues. 82% were motivated to learn more about complementary and integrative medicine and 66% were stimulated to integrate complementary therapies into their professional practice. Conclusion This study from Switzerland confirms the interest in integrative medicine among pediatricians and supports the need for pre- and postgraduate pediatric training on topics related to complementary and integrative medicine. Developing and adapting training and continuing medical education based on evaluations of participant feedback can promote professional development and improve patient care for the benefit of physicians and patients.